NEXUS: a phase I dose escalation study of selinexor plus nivolumab and ipilimumab in Asian patients with advanced/metastatic solid malignancies - Joan R. Choo; Santhiay Nathan Jeraj; Raghav Sundar; Wei Peng Yong; Matilda Lee; Yiqing Huang; Yugarajah Asokumaran; Gloria H. J. Chan; Natalie Y. L. Ngoi; Andrea L. A. Wong; Ross A. Soo; Cheng Ean Chee; et al. (Therapeutic Advances in Medical Oncology)
Background: Selinexor (SEL) is an oral inhibitor of nuclear export protein Exportin 1 (XPO1) previously shown to upregulate programmed cell death protein 1 (PD-L1) and cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) expression. Objective: To investigate the safety and antitumor activity of SEL, nivolumab (NIVO), and ipilimumab (IPI) in Asian patients with treatment-refractory solid organ cancers. Design: Phase I study of escalating doses of SEL in combination with NIVO + IPI. Patients were enrolled in a 3 + 3 design. Methods: NIVO and IPI were dosed at 240 mg Q2W and 1 mg/kg Q6W, respectively. SEL was dosed with a 2-week monotherapy run-in prior to triplet therapy, at dose levels (DL) 1 (40 mg once/week) and DL2 (60 mg once/week). Dose-limiting toxicity (DLT) was assessed over the first 6 weeks. Results: Twelve patients were enrolled; 11 were evaluable for response, and 6 were evaluable for DLT (1 had a non-treatment-related stroke and 5 had progressive disease (PD) prior to completion of the DLT period). The median age was 64.5 (range 39–78) years. The median line of prior therapy was 3 (range 2–5). Dose escalation proceeded through DL1 ( n  = 7, 3 evaluable for DLT) and DL2 ( n  = 5, 3 evaluable for DLT). No DLTs were observed among evaluable patients. No patients required dose reduction of SEL. Most frequent treatment-related AEs were fatigue (5/12; G  ⩾ 3 = 1), nausea (5/12; G  ⩾ 3 = 0), anorexia (4/12; G  ⩾ 3 = 0), transaminitis (2/12; G  ⩾ 3 = 0), and hypomagnesemia (2/12; G  ⩾ 3 = 0). The recommended phase II dose was SEL 60 mg once/week combined with NIVO + IPI. One patient had a partial response (PR; progression-free survival (PFS) of 61 days), 3 had prolonged stable disease (SD; PFS of 141, 344, and 442 days, respectively), and 7 had PD. All patients with SD or PR had previously progressed on immunotherapy but experienced prolonged disease control on SEL in combination with NIVO + IPI. Conclusion: SEL in combination with NIVO + IPI was well tolerated without any new safety signals. The combination showed promising and durable antitumor activity in Asian patients with advanced malignancies who had failed prior immunotherapy and merits further investigation. Trial registration: NCT04850755 ( https://clinicaltrials.gov/study/NCT04850755 ).